(untitled) (Journal of Advanced Veterinary and Animal Research, 2014)
The objective of the present study was to monitor the hypolipidemic and hypocholesterolemic effects of propolis in rats fed high cholesterol diet. The rats (n=32) were divided into four equal groups. The rats of group 1 (control) were fed basal diet, whereas rats of group 2 were fed basal diet mixed with cholesterol (1%). The rats of group 3 and 4 were fed high cholesterol diet (1%) mixed with propolis powder 1 and 2%, respectively. Hematological parameters were comparable among all groups. Cholesterol, triacylglycerol and ALT activities were increased significantly in rat fed high cholesterol diet as compared to control. Inclusion of propolis in high cholesterol diets reduced these parameters in serum. Hematological and biochemical findings were supported by histopathological analysis of liver tissues. Conclusively, 1% propolis was found as safe and enough to induce beneficial hypolipidemic and hypocholesterolemic effects in serum of rats fed high cholesterol diet. http://dx.doi.org/10.5455/javar.2015.b49